COMPARATIVO ENTRE A LOGÍSTICA DE CANTEIROS DE OBRAS DE CONSTRUTORAS COM E SEM CERTIFICAÇÃO DE QUALIDADE - Colatto, Otavio; Manfroi, Eliz (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
Quality programs are often implanted in construction companies to help the logistics within the jobsite to be improved, ensuring quality in the product and a reduced cost. However, not all companies adopt these programs but they achieve good results by applying good internal logistics within their works. In this context, in this research was done a relation of the logistics of construction sites in construction companies that use quality programs and in construction companies that don't use the same. Thus, it was drawn up a checklist and performed periodic visits in the four construction sites that were evaluated, in order to compare the performance of the logistics among them in each sector. At the end of this work, it can be verified that the construction sites that had a quality program presented better logistical performance.